Epigenetics in Schistosomes: What We Know and What We Need Know - Liu, Weiwei (Frontiers in Cellular and Infection Microbiology, 2016)
Schistosomes are metazoan parasites and can cause schistosomiasis. Epigenetic modifications include DNA methylation, histone modifications and non-coding RNAs. Some enzymes involved in epigenetic modification and microRNA processes have been developed as drugs to treat the disease. Compared with humans and vertebrates, an in-depth understanding of epigenetic modifications in schistosomes is starting to be realized. DNA methylation, histone modifications and non-coding RNAs play important roles in the development and reproduction of schistosomes and in interactions between the host and schistosomes. Therefore, exploring and investigating the epigenetic modifications in schistosomes will facilitate drug development and therapy for schistosomiasis. Here, we review the role of epigenetic modifications in the development, growth and reproduction of schistosomes, and the interactions between the host and schistosome. We further discuss potential epigenetic targets for drug discovery for the treatment of schistosomiasis.